FRESH AND CRYOPRESERVED SEMEN CHARACTERISTICS OF BUFFALO BULLS AS INFLUENCED BY MELATONIN IMPLANTATION - Z. M. Nsaif; S. M. Eidan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study explored the effect of melatonin implantation on the fresh and cryopreserved semen quality of Iraqi buffalo bulls (Bubalus bubalis). Nine adult bulls were used and divided equally into three groups. The first group was left without treatment and regarded as control (T1), whereas the second (T2) and third (T3) groups were subcutaneously implanted with 72 and 90 mg of melatonin respectively on the left ear base and repeated one month post the first implantation. Semen was collected for 12 weeks and evaluated weekly for fresh, cooling, and post-cryopreserved (PC) protocols. The T3 group exhibited a higher (P≤0.05) sperm cell individual motility percentage, whereas, the T1 and T2 groups recorded better (P≤0.05) sperm acrosome integrity percentage for fresh semen. A lesser (P≤0.05) total sperm abnormality (TSA) percentage in the T2 and T3 groups and a greater (P≤0.05) sperm acrosome integrity (SAI) percentage in the T3 group were noticed during the cooling preservation. Moreover, the T3 group exhibited a lesser (P≤0.05) TSA percentage whereas, the T2 and T3 groups revealed a leaser (P≤0.05) SAI percentage during the PC period. Concomitantly, lower (P≤0.05) PC malondialdehyde concentration in seminal plasma was observed in the T2 and T3 groups than control group. In conclusion, the melatonin implantation (72 and 90 mg) ameliorated some fresh and PC semen attributes of the Iraqi buffalo bulls.